Bence-Jones protein as the form of nano-scaled β-stacked supramolecular aggregates - Voroshylova, N. M.; Timchenko, M. D.; Verevka, S. V. (Ukrainian Journal of Nephrology and Dialysis, 2019)
Abstract. The formation in β-structured protein aggregates in tissues and fluids of the body is one of the most dangerouse complications of various diseases. The most famous of them are amyloidoses, but they such deposits are observed at other, much more widespread, diseases. The generally accepted approach to amyloids’detectionis based on high-specific coloring by Congo Red dye. However, the Abbe’s diffraction limit excludes the seeing of the objects smaller than 0.61 wavelengths (about 240 nm). Such nanoscale formations are capable to disrup the functioning of surrounding tissues, to causethe complications and recurrences of the disease, and to pass through biological barriers with the following accumulation in body’s fluids. It’s likely that these conditions are the cause of the urinary congophilia, that is associated with preeclampsia at pregnancy and chronic kidney disease. Nor the less suspicious object is the Bens-Jones protein that appears in the urine at multiple myeloma and some other diseases, which are in more or less extent,are related to the disturbance of protein metabolism. The purpose of this study was to clarify the aggregate state of the Bens-Jones protein as a possible β-structured supramolecular associate. Methods.The subject of the study was the freshly received urine from a patient with multiple myeloma. The presence of the Bens-Jones protein was checked by thermopacification of the acidified sample. For control, the urine was used by a healthy person with the addition of certain amounts of human serum albumin ("Reanal", Hungary) with a concentration of 0, 0.01, 0.1 and 1%. Result. The obtained data testify to the appropriateness of such a point of view and create preresquites for the expanding of diagnostic possibilities. Conclusions.The results obtained during the study testify to the peculiarity of the structure of the Bens-Jones protein, which is nano-sized beta-structured supramolecular